PENGUATAN EKONOMI PESANTREN MELALUI DIGITALISASI UNIT USAHA PESANTREN - Muh. Hamzah; Achmad Febrianto; Ainol Yakin; Siti Nurbayah; Septian Fiktor Riyantoro (ITB AAS INDONESIA Surakarta, 2022)
This study uses a qualitative method, namely a descriptive approach because this approach always provides the basis and convenience in an effort to achieve the goal optimally. The reasons that encourage researchers to use this method are to answer various questions and problems about the role of parent cooperatives in improving the Economics of Islamic Boarding Schools in the Az-Zainiyah Region. Data collection technique is the method taken by researchers in collecting research data, in accordance with the form of the qualitative approach and data sources used, so this technique uses direct observation or observation in order to obtain an accurate picture of the matters being studied. The results of this study indicate that the strengthening of the pesantren economy through digitizing the pesantren business unit with the existence of E-Bekal is always real for its contribution, besides that using E-Bekal makes it easier for cooperative members in finance, by providing income that is donated to Islamic boarding schools in the Region. Az-Zainiyah, this study also describes the Parent Cooperative which provides needs for students of the Az-Zainiyah Region in the form of daily needs such as toiletries, school needs, etc., as well as supporting the existing infrastructure in the pesantren. Keywords: Economy, Digitalization, Islamic Boarding School